Ethno-medicinal survey of weeds of Changa Manga forest, Pakistan - Fatima, Bilqees; Akram, Sadia; Khan, Zaheer-ud-din; Javed, Muhammad Mohsin (Ethnobotany Research and Applications, 2025)
Background: Keeping in mind the popularity of using local flora in the traditional health care system, the present study was designed to document the ethnomedicinal data on the common weeds of a well-known man-made forest at Changa Manga town, tehsil Chunia, district Kasur, Punjab, Pakistan. The study aimed to widen the status of weeds as a primary healthcare resource to renovate the pharmacopeia in Pakistan. Methods: In this study a total of 49 ethnomedicinally important weed species belonging to 30 families were collected from Changa Manga forest. The study area was partitioned into four blocks. A shed colony region and the vicinity of Change Manga Lake were also included. In a survey, the data was collected through standardized questionnaires about traditional therapies of the collected weeds from 100 informants, among whom 40 were traditional practitioners and 60 were indigenous people. Results: The collected data was quantitatively analyzed through indices like relative frequency of citation (RFC = 0.09-0.44), use value (UV = 0.02-0.18), fidelity level (FL = 38-100 %), and informant census factor (ICF = 0.72-0.3). Results showed that the Solanaceae family’s weeds comparatively have the utmost use for different therapies in this area. Leaves are the highly used part of the plants for medicines. Mostly the medicines are formulated in the form of an extract and a paste. Gastrointestinal disorders are the most dominantly treated by ethnomedicines in the region Conclusion: It is concluded that people acknowledged the medicinal significance of weeds and have believed in traditional ethnomedicines even in this modern era. However, there is an un-availability of scientific information and guidelines regarding the safety and efficiency of herbal medicines. This fact hinders the large-scale promotion and development of herbal therapies. So, the merging of indigenous knowledge with modern therapeutic practices is a great need of this era. This lineal knowledge also needs scientific documentation and validation. Keywords: Ethnomedicinal survey, Medicinal weeds, Changa Manga forest, Medicinal weeds, Pharmacopeia, Medical anthropology, Traditional use.